Kedisiplinan guru: studi kasus SMA Negeri 2 Purworejo - -, Suhada; Purbonuswanto, Welius (Universitas Sebelas Maret, 2021)
The objectives to be achieved in this study, (1) describe the characteristics of teacher discipline in learning administration at SMA Negeri 2 Purworejo. (2) describe the characteristics of teacher discipline in learning at SMA Negeri 2 Purworejo. (3) describe the characteristics of teacher discipline in the evaluation of learning at SMA Negeri 2 Purworejo. The results showed that, (1) the characteristics of teacher disciplinary violations in SMA Negeri 2 Purworejo. The types of disciplinary violations that are mostly done by teachers are minor disciplinary violations, with punishments in the form of verbal warnings, written warnings, and written statements of dissatisfaction. The type of minor disciplinary violation does not rule out the possibility of turning into a moderate type of disciplinary violation. For disciplinary violations in the severe category, there were no teachers who committed serious disciplinary violations. For serious disciplinary violations, if the violator commits a criminal act that has received a permanent judge's decision, the sanction is in the form of dismissal from office. (2) the characteristics of teacher discipline enforcement at SMA Negeri 2 Purworejo. Efforts made by schools to prevent violations committed by teachers are to carry out socialization of laws and regulations concerning the implementation of civil servant discipline or teachers, provide regular and continuous guidance to teachers, and carry out supervision. To prevent disciplinary violations from occurring again, the school provides strict sanctions to disciplinary violators in accordance with the disciplinary violations committed.